Ultrasound-Mediated Blood-Brain Barrier Disruption for Drug Delivery: A Systematic Review of Protocols, Efficacy, and Safety Outcomes from Preclinical and Clinical Studies - Kushan Gandhi; Anita Barzegar-Fallah; Ashik Banstola; Shakila B. Rizwan; John N. J. Reynolds (MDPI AG, 2022)
Ultrasound-mediated blood-brain barrier (BBB) disruption has garnered focus as a method of delivering normally impenetrable drugs into the brain. Numerous studies have investigated this approach, and a diverse set of ultrasound parameters appear to influence the efficacy and safety of this approach. An understanding of these findings is essential for safe and reproducible BBB disruption, as well as in identifying the limitations and gaps for further advancement of this drug delivery approach. We aimed to collate and summarise protocols and parameters for achieving ultrasound-mediated BBB disruption in animal and clinical studies, as well as the efficacy and safety methods and outcomes associated with each. A systematic search of electronic databases helped in identifying relevant, included studies. Reference lists of included studies were further screened to identify supplemental studies for inclusion. In total, 107 articles were included in this review, and the following parameters were identified as influencing efficacy and safety outcomes: microbubbles, transducer frequency, peak-negative pressure, pulse characteristics, and the dosing of ultrasound applications. Current protocols and parameters achieving ultrasound-mediated BBB disruption, as well as their associated efficacy and safety outcomes, are identified and summarised. Greater standardisation of protocols and parameters in future preclinical and clinical studies is required to inform robust clinical translation.